2016
DOI: 10.1136/jech-2016-207307
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends in physical fitness and body size in Lithuanian children and adolescents between 1992 and 2012

Abstract: The general decline in physical fitness in Lithuanian schoolchildren observed between 1992 and 2002 continued between 2002 and 2012, although some aspects of fitness showed a positive trend. If this general negative trend continues, it will compromise the well-being of future adults and create a serious economic burden on the society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
148
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(176 citation statements)
references
References 31 publications
19
148
2
7
Order By: Relevance
“…A majority of the studies monitoring muscular fitness trends over time have focused on children. Most of these studies show a decreasing trend in muscular fitness, 10,11,[21][22][23] although, similar to the present study findings, no changes have also been observed, 24,25 while one study reported an increase. 26 Furthermore, the mean sit-up results were 37 reps/ min for 18-20 years Finnish men 7 and 34-38 repetitions in present 5-10 years older study sample.…”
Section: Discussionsupporting
confidence: 85%
“…A majority of the studies monitoring muscular fitness trends over time have focused on children. Most of these studies show a decreasing trend in muscular fitness, 10,11,[21][22][23] although, similar to the present study findings, no changes have also been observed, 24,25 while one study reported an increase. 26 Furthermore, the mean sit-up results were 37 reps/ min for 18-20 years Finnish men 7 and 34-38 repetitions in present 5-10 years older study sample.…”
Section: Discussionsupporting
confidence: 85%
“…The magnitudes of these secular increases were broadly comparable in magnitude to those reported in other European children over the past two decades 7,9 . The combination of increases in both measures provide evidence for an overall increase in body size for children of this age which is evident from the year-olds from this affluent area 11 .…”
Section: Discussionsupporting
confidence: 78%
“…These findings suggest the influence of alternative factors, such as muscle mass, metabolic capacity or neural drive. Declines in sit-ups test performance have been reported previously 7,8,11 as have downward temporal trends in bent-arm hang 8 12 . Contrary trends in sit-ups performance have been reported in Greek 28 and Portuguese 9 children but, to our knowledge, no studies have reported improvements in bent-arm hang.…”
Section: Discussionmentioning
confidence: 65%
“…A negative trend in most aspects of physical fitness, as observed in school‐aged children over a 20‐year interval, is a worrying health trend all over the world and will compromise well‐being of future adults . Modern children have lower physical activity than the children of a decade ago as a result of less time being spent playing outdoors or active transport to school .…”
Section: Discussionmentioning
confidence: 99%